Morphology and pomological characterization of bael [Aegle marmelos (L.) Correa] genotypes for climate change mitigation under north-western Himalayas - Singh, Prabhdeep; Sharma, Akash; Gupta, Sushil Kumar; Salgotra, Romesh Kumar; Gupta, Vishal; Sharma, Manish (Frontiers in Plant Science, 2025)
This study investigated the genetic diversity of 80 wild bael genotypes (Aegle marmelos) compared to commercial cultivars NB-5 and NB-9, focusing on 16 pomological traits. With the rising temperature impacting perennial fruit crop production and the urgent need for heat- and drought-resistant varieties, bael emerges as a viable option for rainfed areas due to its xerophytic characteristics and ability to withstand high temperatures. Among the collected, wild bael genotype germplasm, JMU-Bael (Sel-27) demonstrated superior traits, including maximum fruit length (12.05 cm), width (11.72 cm), weight (917.65 g), pulp weight (746.81 g), and pulp percentage (81.38%). Correlation matrices revealed significant associations among pomological traits, particularly positive correlations with fruit weight. Principal component analysis (PCA) indicated substantial genetic diversity, with the first two components explaining 63.98% of the cumulative variation. Cluster analysis grouped genotypes into two main clusters, providing insights into their diversity and potential breeding applications. This comprehensive analysis offers valuable insights into the genetic variability and adaptability of bael genotypes under changing climatic conditions in the plains of north-western Himalayan regions.